2016
DOI: 10.1016/j.jprot.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking quantitative label-free LC–MS data processing workflows using a complex spiked proteomic standard dataset

Abstract: Bioinformatic pipelines for label-free quantitative analysis must be objectively evaluated in their ability to detect variant proteins with good sensitivity and low false discovery rate in large-scale proteomic studies. This can be done through the use of complex spiked samples, for which the "ground truth" of variant proteins is known, allowing a statistical evaluation of the performances of the data processing workflow. We provide here such a controlled standard dataset and used it to evaluate the performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 41 publications
4
81
0
Order By: Relevance
“…3). Results from both experiments were complementary and showed that LC-MS ion intensity protein abundance measurements outperformed spectral counting in terms of accuracy and precision, and supported recent studies comparing both label-free methods in the estimation of absolute protein abundances [5,7,[27][28][29]. Moreover, although both labelfree quantification methods responded linearly to increasing protein concentration, protein quantification measurements changed at almost the same rate for LC-MS ion intensity quantification but not spectral counting, suggesting that LC-MS ion intensity quantification is fairly robust to differences in physicochemical properties of peptides, number of peptides per proteins, and ionisation efficiencies of peptides.…”
Section: Discussionsupporting
confidence: 72%
“…3). Results from both experiments were complementary and showed that LC-MS ion intensity protein abundance measurements outperformed spectral counting in terms of accuracy and precision, and supported recent studies comparing both label-free methods in the estimation of absolute protein abundances [5,7,[27][28][29]. Moreover, although both labelfree quantification methods responded linearly to increasing protein concentration, protein quantification measurements changed at almost the same rate for LC-MS ion intensity quantification but not spectral counting, suggesting that LC-MS ion intensity quantification is fairly robust to differences in physicochemical properties of peptides, number of peptides per proteins, and ionisation efficiencies of peptides.…”
Section: Discussionsupporting
confidence: 72%
“…However, we have provided a separate table (Additional file 2: Table S2) that filters differentially expressed proteins by both Welch’s t test as well as z -score (see the “Methods” section). This type of filtering approach has been shown to be less stringent than multiple testing correction methods (e.g., Bonferroni or Benjamini-Hochberg) while still maintaining adequate FDR and sensitivity [43]. Several differentially expressed proteins (out of 156 total differentially expressed proteins from the second filtering approach) related to microglial function are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Meta-omic count data were assumed to be modeled by a beta binomial distribution based on previous studies performed on count data obtained through discovery mass spectrometry proteomics (Ramus et al, 2016) and nucleic acid sequencing techniques (Smith and Birtwistle, 2016). The p -value list provided by the ibb test was subsequently subjected to a multiple testing adjustment based on a sequential goodness of fit (SGoF) metatest (Carvajal-Rodriguez et al, 2009) using the SGoF+ software (v.3.8) with default parameters (Carvajal-Rodriguez and de Una-Alvarez, 2011).…”
Section: Methodsmentioning
confidence: 99%